Brachyrhynchoides nom. nov. Artois & Schockaert, 2013: A replaced name for Brachyrhynchus Artois & Schockaert, 2013 - Artois, Tom; Willems, Wim; Reygel, Patrick; Schockaert, Ernest (Zootaxa, 2013)
We herewith propose that the genus Brachyrhynchus Artois & Schockaert, 2013, be renamed Brachyrhynchoides nom. nov. Artois & Schockaert, 2013.Immediately after publication of Brachyrhynchus Artois & Schockaert, 2013 (Rhabdocoela), we were kindly notified by a colleague that the name is preoccupied, being a junior synonym of Brachyrhynchus Dejean, 1821 (Coleoptera). Although we did check in the Index to Organism Names (ION; Thomson Reuters 2009) and the Global Names Index (http://gni.globalnames.org/) before submitting the manuscript, Brachyrhynchus did not gave any results, possibly because of an unfortunate writing mistake in the search string. Apart from Brachyrhynchus Artois & Schockaert, 2013, there are four other junior synonyms of Brachyrhynchus Dejean, 1821: Brachyrhynchus Laporte, 1833 (Hemiptera), Brachyrhynchus Fitzinger, 1843 (Reptilia), Brachyrhynchus Selys, 1842 (Aves) and Brachyrhynchus Van Beneden, 1871 (Teleostei). There seems to be an ambiguity about the publication date of Brachyrhynchus Laporte, which is given as 1832 by ION and GNI, but apparently should be 1833 according to Cassis & Gross (2002), who follow Direction 63/1956 of the International Commission of Zoological Nomenclature (see Cassis & Gross, 2002: p.48). We therefore propose to replace the name Brachyrhynchus Artois & Schockaert, 2013 by Brachyrhynchoides nom. nov.